Farming system design for innovative crop-livestock integration in Europe. (20th May 2014) - Moraine, M.; Duru, M.; Nicholas, P.; Leterme, P.; Therond, O.
<x content-type="archive" xml:space="preserve">Abstract</x> The development of integrated crop–livestock systems (ICLS) is a major challenge for the ecological modernisation of agriculture but appears difficult to implement at a large scale. A participatory method for ICLS design has been developed and implemented in 15 case studies across Europe, representing a range of production systems, challenges, constraints and resources for innovation. Local stakeholders, primarily farmers, but also cooperatives, environmental-association representatives and natural-resource managers, were involved in the identification of challenges and existing initiatives of crop-livestock integration; in the design of new options at field, farm and territory levels; and then in qualitative multicriteria assessment of these options. A conceptual framework based on a conceptual model (crops, grasslands, animals) was developed to act as a boundary object in the design step and invite innovative thinking in 'metabolic' and 'ecosystemic' approaches. A diversity of crops and grasslands interacting with animals appeared central for designing sustainable farming systems at the territory level, providing and benefitting from ecosystem services. Within this diversity, we define three types of integrated systems according to their degrees of spatial and temporal coordination: complementarity, local synergy, territorial synergy. Moreover, the options for cooperation and collective organisation between farmers and other stakeholders in territories to organise and manage this diversity of land use revealed opportunities for smart social innovation. The qualitative multicriteria assessment identified farmer workload as the main issue of concern while demonstrating expected benefits of ICLS simultaneously for economic, agronomic, environmental and social criteria. This study concludes that participatory design of ICLS based on a generic multi-level and multi-domain framework and a methodology to deal with a local context can identify new systems to be tested. Further assessment and redesign work will be performed in later stages of the European FP7 CANTOGETHER project.